Membangun Karakter Gemar Menabung dan Edukasi Keuangan Syariah bagi Pelajar di Desa Perkebunan Gunung Melayu - Yasmine Sabila Hawani; Ahmad Afandi (Lembaga Pengembangan Kinerja Dosen, 2025)
This Independent Community Service Program (KKN Mandiri) was conducted to foster the habit of saving and to enhance students’ understanding of the fundamental principles of Islamic finance in Gunung Melayu Plantation Village, Rahuning District, Asahan Regency, North Sumatra Province. The program was designed as an educational-based community engagement activity involving students, teachers, and local residents. The implementation methods included educational approaches such as socialization, counseling, interactive discussions, saving practice sessions, and community service activities as collaborative learning media. The results revealed a significant improvement in students’ awareness of the importance of saving from an early age, their ability to manage pocket money effectively, and their understanding of Islamic financial values such as the prohibition of riba (usury), fairness in transactions, and the importance of seeking blessings in wealth. Furthermore, this program strengthened community and school participation in supporting sustainable Islamic financial literacy initiatives. Overall, the KKN activity had a positive impact on shaping students’ financial intelligence, discipline, and Islamic moral character.